2017
DOI: 10.1371/journal.pone.0169469
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Upregulates Adiponectin Level in Adipocytes via Sirt1/Foxo-1 Signaling Pathway

Abstract: Glucagon-like peptide-1 (GLP-1) receptor plays an essential role in regulating glucose metabolism. GLP-1 receptor agonists have been widely used for treating diabetes and other insulin resistance-related diseases. However, mechanisms underlying the anti-diabetic effects of GLP-1 receptor agonists remain largely unknown. In this study, we investigated the effects of GLP-1 agonist exendin-4 on the expression of adiponectin, an insulin sensitizing hormone. We found that exendin-4 increased the expression and secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 19 publications
(37 reference statements)
3
31
0
Order By: Relevance
“…Several studies have shown that Ex4 induced increased adiponectin levels, directly promotes adiponectin secretion in adipocytes and improves insulin sensitivity (Kim Chung et al, 2009;Li et al, 2008;Pastel et al, 2016;Wang et al, 2017). Moreover, improving adiponectin levels with Ex4 treatment correlated with improved learning ability, which is consistent with studies showing a role of adiponectin in cognitive impairments (Kim et al, 2017;Ng et al, 2016;Wang, Jo, & Song, 2019;Zhang et al, 2017).…”
Section: Ex4 Treatmentsupporting
confidence: 83%
“…Several studies have shown that Ex4 induced increased adiponectin levels, directly promotes adiponectin secretion in adipocytes and improves insulin sensitivity (Kim Chung et al, 2009;Li et al, 2008;Pastel et al, 2016;Wang et al, 2017). Moreover, improving adiponectin levels with Ex4 treatment correlated with improved learning ability, which is consistent with studies showing a role of adiponectin in cognitive impairments (Kim et al, 2017;Ng et al, 2016;Wang, Jo, & Song, 2019;Zhang et al, 2017).…”
Section: Ex4 Treatmentsupporting
confidence: 83%
“…Dulaglutide significantly upregulated the expression of Hsp72 protein in both GA and soleus muscles. As SIRT1 is an upstream target of Hsp72 (Wang et al, 2017) and the induction of SIRT1 expression in the skeletal muscle is related to the activation of AMPK molecule (Lin and Huang, 2016), we hypothesized that the dulaglutide-mediated increase in Hsp72 expression level in the skeletal muscle may be mediated by AMPK activation. The results observed with AMPK inhibitor treatment show that the increase in Hsp72 protein expression after exposure to dulaglutide or Ex-4, GLP-1 receptor agonist, in C2C12 myotubes was regulated by AMPK ( Figures 6F, H).…”
Section: Discussionmentioning
confidence: 99%
“…Dulaglutide also increased Hsp72 expression in the GA muscle of the non-immobilized control mice ( Figures 6A, B). Hsp72 expression is regulated by sirtuin 1 (SIRT1) (Wang et al, 2017), and GLP-1 receptor agonist could activate SIRT-1 through the induction of AMPK signaling (Lin and Huang, 2016). Therefore, we investigated the effect of dulaglutide or Ex-4 on Hsp72 and p-AMPK expression in C2C12 myotubes in vitro.…”
Section: Dulaglutide Treatment Increased the Expression Of Hsp72 Thromentioning
confidence: 99%
“…Several other ECM components, such as secreted protein acidic and rich in cysteine (54,55), biglycan (56), heparan sulfate proteoglycans (57,58), aggrecan (59), entactin (60), laminin (60)(61)(62), and extendin-4 (63,64), also have described roles in adipogenesis. In this Review, we will focus mainly on the involvement of collagens and collagen-cleaving enzymes in obesity-associated metabolic dysfunction.…”
Section: Components Of Adipose Tissue Ecmmentioning
confidence: 99%